Insights into perceptions, responses, and challenges experienced by women and girls' survivors of sexual violence and their communities in rural Guinea, 2020 - Delphin Kolié; Delphin Kolié; Abdoulaye Sow; Abdoulaye Sow; Graziella Ghesquiere; Stefaan Van Bastelaere; Maurice Sandouno; Thierno Souleymane Diallo; Sabine Soropogui; Yaya Barry; Thierno Oumar Fofana; Bienvenu Salim Camara; et al. (Frontiers Media S.A., 2024)
IntroductionGender-based violence (GBV), particularly sexual violence, is a significant global public health issue with severe physical, psychological, and social consequences for survivors and their communities, especially among women and girls. In Guinea, limited data exist on the frequency and management of sexual violence in rural areas. This study aimed to analyze the perceptions, responses, and challenges faced by women and girls' survivors of sexual violence and their communities in two rural districts of Guinea in 2020.MethodsA parallel mixed-methods approach was employed, integrating quantitative and qualitative data. For the quantitative analysis, all reported cases of GBV from public health facilities and directorates of girls and women' promotion were collected from January 1 to December 31, 2020 in the health districts of Télimélé and Mamou. The qualitative component involved key informant interviews with four main participant groups: survivors of GBV and their support networks, healthcare providers, stakeholders and partners involved in GBV prevention and response, and community leaders. Data were analyzed to identify patterns in case reporting, perceptions of violence, responses by survivors and communities, and challenges to effective management.ResultsThe study revealed a high frequency of reported sexual violence among women, with substantial disparities between the two districts. In Mamou, sexual violence among women constituted 61% of all reported GBV cases, whereas in Télimélé, it accounted for only 8%. Additionally, data on sexual violence were inconsistent, with discrepancies in terminology and significant underreporting of cases. Survivors and their families predominantly sought conciliation with perpetrators' families, motivated by fear of retaliation, social stigmatization, and exclusion. This response was more prevalent in communities with limited law enforcement, where perpetrators were often released after short periods of detention. Participants highlighted several barriers to accessing health services and providing comprehensive care to survivors. These barriers included socio-economic constraints, a lack of skilled healthcare providers, frequent stock-outs of essential medical supplies, and the absence of psycho-social and legal support at the community level.ConclusionThe findings highlight the urgent need to enhance the capacity of decentralized health and social services to deliver integrated, patient-centered care for sexual violence. There is also a pressing need for stronger enforcement of laws related to sexual violence, enhanced training for healthcare providers, and the harmonization of GBV data reporting tools. Tackling socio-cultural barriers through community education, while enhancing access to legal and psychological support are crucial for reducing the frequency of sexual violence and ensuring timely, quality care for survivors in Guinea.